2014
DOI: 10.4300/jgme-d-13-00179.1
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of the Family Educational Rights and Privacy Act and the Standardized Letter of Recommendation: Impact on Emergency Medicine Residency Applicant and Faculty Behaviors

Abstract: The majority (93%) of residency applicants waived their FERPA rights. Those who did not waive their rights had a statistically higher chance of receiving an Outstanding Assessment than those who did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The bulk of applicants to 14 EM programs (93%) waived their FERPA rights to see their SLORs or NLORs. In one multicenter study, applicants who retained their FERPA rights were more likely to receive a GAS of ''Outstanding'' than those who did waive their rights, although this retrospective study had numerous limitations identified by the authors (24).…”
Section: Should I Waive My Right To See the Letter?mentioning
confidence: 97%
“…The bulk of applicants to 14 EM programs (93%) waived their FERPA rights to see their SLORs or NLORs. In one multicenter study, applicants who retained their FERPA rights were more likely to receive a GAS of ''Outstanding'' than those who did waive their rights, although this retrospective study had numerous limitations identified by the authors (24).…”
Section: Should I Waive My Right To See the Letter?mentioning
confidence: 97%
“…Approximately 93% of students waive their rights to view the SLOE. 10 Mechanisms such as on-shift, midclerkship, and end-of-rotation feedback could provide students with insight into their own performance and allow for an accurate appraisal of their overall competitiveness as an EM applicant. However, whether performance feedback given to students during and after their clerkship translates into accurate self-assessment has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, although they have been discussed for several years, they have yet to be adopted uniformly in otolaryngology, and opinions and experiences in other specialties vary. [10][11][12][13] Moreover, unless these standardized letters include or are supplemented by free-form commentary, much of the most valuable, personal information about applicants may not be conveyed well enough. In addition, it seems unlikely that this approach will reduce the number of applications per candidate.…”
mentioning
confidence: 99%